In vitro potency and combination testing of antimicrobial agents against Neisseria gonorrhoeae. Issue 3 (March 2016) - Bharat, Amrita; Martin, Irene; Zhanel, George G.; Mulvey, Michael R.
Abstract: Antimicrobial resistant Neisseria gonorrhoeae is a major concern to public health due to decreased susceptibility to frontline antimicrobials. To find agents that are active against N. gonorrhoeae, we tested antimicrobials alone or in combination by Etest gradient strips. The potencies (as assessed by minimum inhibitory concentrations) of twenty-five antimicrobials were evaluated against nine reference strains of N. gonorrhoeae (WHO F, G, K, L, M, N, O, P and ATCC 49226). Potency was greatest for netilmicin, quinupristin-dalfopristin, ceftriaxone, ertapenem and piperacillin-tazobactam. Combinations of azithromycin, moxifloxacin, or gentamicin with ceftriaxone, doripenem, or aztreonam were tested against reference isolates and the fractional inhibitory concentration index (FICI) was calculated. All nine combinations resulted in indifference (>0.5 FICI ≤ 4). Combinations with FICI < 1 were further evaluated in nine clinical isolates which supported the finding of indifference. No antagonism was observed in any of the combinations tested. This is the first report in which the six combinations of azithromycin, moxifloxacin or gentamcin in combination with doripenem or aztreonam were tested in N. gonorrhoeae . These data on antimicrobials with higher potency and combinations that did not show antagonism can help to guide larger scale susceptibility studies for antimicrobial resistant N. gonorrhoeae .